(untitled) (Analytical Methods for Drug Development, 2025)
Author Mrs Nagalakshmi Konarachapalle Assistant Professor, Department of Pharmaceutical Chemistry, Annamacharya College of Pharmacy, Thallapaka, Rajampet, Andhra Pradesh, India Abstract Chromatographic methods separate complex pharmaceutical mixtures based on differential interactions between components, mobile phases, and stationary phases. HPLC techniques utilize diverse separation mechanisms, stationary phases, mobile phase compositions, and detection systems for pharmaceutical assays, impurity profiling, and stability studies. Gas chromatography analyzes volatile compounds, residual solvents, and headspace samples with temperature programming, specialized columns, and various detection systems. Ion chromatography quantifies counterions, ionic impurities, and ionic formulation components using suppressed and non-suppressed systems for pharmaceutical quality control. Size exclusion chromatography determines molecular weight distributions for polymers, proteins, and aggregates in biopharmaceuticals through calibration with reference standards. Method development strategies apply quality by design principles with experimental design, critical parameter identification, and robustness testing to optimize separations. Keywords: HPLC, Residual solvents, Ion analysis, Protein characterization, Method optimization VIEW PDF